2017
DOI: 10.2337/db16-1182
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a Mimics Reduce the Peripheral Neuropathy in Type 2 Diabetic Mice

Abstract: MicroRNA-146a (miR-146a) regulates multiple immune diseases. However, the role of miR-146a in diabetic peripheral neuropathy (DPN) has not been investigated. We found that mice (db/db) with type 2 diabetes exhibited substantial downregulation of miR-146a in sciatic nerve tissue. Systemic administration of miR-146a mimics to diabetic mice elevated miR-146a levels in plasma and sciatic nerve tissue and substantially increased motor and sensory nerve conduction velocities by 29 and 11%, respectively, and regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 47 publications
9
94
0
Order By: Relevance
“…In addition, miR-146a is consistently dysregulated in T1DM patients ( 49 ). In mice with T2DM, miR-146a mimics significantly ameliorated peripheral neuropathy, principally by suppressing the expression of hyperglycemia-induced proinflammatory genes ( 50 ). Moreover, miR-146a is reportedly involved in high-glucose-induced endothelial inflammation, which suggests that it may be a novel therapeutic target for diabetic vascular disease ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-146a is consistently dysregulated in T1DM patients ( 49 ). In mice with T2DM, miR-146a mimics significantly ameliorated peripheral neuropathy, principally by suppressing the expression of hyperglycemia-induced proinflammatory genes ( 50 ). Moreover, miR-146a is reportedly involved in high-glucose-induced endothelial inflammation, which suggests that it may be a novel therapeutic target for diabetic vascular disease ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers have linked miRNA expression with the pathogenesis of DPN. For instance, miR-146a overexpression was able to inhibit DPN progression through increasing neurological function and reducing inflammatory response [15]. Likewise, miR-25 acted as a protective gene in DPN to reduce the generation of ROS [16].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in miR-146a in diabetic patients and animals were reported in a previous study. Liu et al [25] demonstrated that treatment of diabetic mice with miR-146a mimics robustly reduced diabetic peripheral neuropathy. Then, the target genes of hsa-miR-146a-3p were identified based on the parallel DEmRNAs in the present study.…”
Section: Resultsmentioning
confidence: 99%